Hydrogen sulfide, a potential novel drug, attenuates concanavalin A-induced hepatitis - Cheng P; Chen K; Xia Y; Dai WQ; Wang F; Shen M; Wang C; Yang J; Zhu R; Zhang H; Li JJ; Zheng Y; et al. (Dove Medical Press, 2014)
Ping Cheng,* Kan Chen,* Yujing Xia, Weiqi Dai, Fan Wang, Miao Shen, Chengfen Wang, Jing Yang, Rong Zhu, Huawei Zhang, Jingjing Li, Yuanyuan Zheng, Junshan Wang, Yan Zhang, Jie Lu, Yingqun Zhou, Chuanyong GuoDepartment of Gastroenterology, Shanghai Tenth People's Hospital, Tongji University of Medicine, Shanghai, People's Republic of China *These authors contributed equally to this work Background: Hydrogen sulfide (H2S) is known to exert anti-inflammatory properties. Apoptosis and autophagy play important roles in concanavalin A (Con A)-induced acute hepatitis. The purpose of this study was to explore both the effect and mechanism of H2S on Con A-induced acute hepatitis. Methods: BALB/c mice were randomized into sham group, Con A-injection group, and 14 µmol/kg of sodium hydrosulfide (NaHS, an H2S donor) pretreatment group. Results: Aspartate aminotransferase, alanine aminotransferase, and pathological damage were significantly ameliorated by NaHS pretreatment. NaHS pretreatment significantly reduced the levels of interleukin-6 and tumor necrosis factor-α compared with those of the Con A group. The expression of Bcl-2, Bax, Beclin-1, and LC3-2, which play important roles in the apoptosis and autophagy pathways, were also clearly affected by NaHS. Furthermore, NaHS affected the p-mTOR and p-AKT. Conclusion: H2S attenuates Con A-induced acute hepatitis by inhibiting apoptosis and autophagy, in part, through activation of the PtdIns3K-AKT1 signaling pathway. Keywords: NaHS, apoptosis, PtdIns3K-AKT, autophagy